Managing the Canadian Mosaic in Wartime: Shaping Citizenship Policy, 1939-1945 - Loewen, Royden (Labour / Le Travail, 2011)
The article reviews the book, "Managing the Canadian Mosaic in Wartime: Shaping Citizenship Policy, 1939-1945," by Ivana Caccia.
Keywords: 1914-1945; BOOKS -- Reviews; CACCIA, Ivana; Canada; History; MANAGING the Canadian Mosaic in Wartime: Shaping Citizenship Policy 1939-1945 (Book); Nonfiction